The Vampirome: Transcriptome and proteome analysis of the principal and accessory submaxillary glands of the vampire bat Desmodus rotundus, a vector of human rabies - Francischetti, Ivo M.B.; Assumpção, Teresa C.F.; Ma, Dongying; Li, Yuan; Vicente, Eliane C.; Uieda, Wilson [UNESP]; Ribeiro, José M.C. (Elsevier, 2013)
Vampire bats are notorious for being the sole mammals that strictly feed on fresh blood for their survival. While their saliva has been historically associated with anticoagulants, only one antihemostatic (plasminogen activator) has been molecularly and functionally characterized. Here, RNAs from both principal and accessory submaxillary (submandibular) salivary glands of Desmodus rotundus were extracted, and ~. 200. million reads were sequenced by Illumina. The principal gland was enriched with plasminogen activators with fibrinolytic properties, members of lipocalin and secretoglobin families, which bind prohemostatic prostaglandins, and endonucleases, which cleave neutrophil-derived procoagulant NETs. Anticoagulant (tissue factor pathway inhibitor, TFPI), vasodilators (PACAP and C-natriuretic peptide), and metalloproteases (ADAMTS-1) were also abundantly expressed. Members of the TSG-6 (anti-inflammatory), antigen 5/CRISP, and CCL28-like (antimicrobial) protein families were also sequenced. Apyrases (which remove platelet agonist ADP), phosphatases (which degrade procoagulant polyphosphates), and sphingomyelinase were found at lower transcriptional levels. Accessory glands were enriched with antimicrobials (lysozyme, defensin, lactotransferrin) and protease inhibitors (TIL-domain, cystatin, Kazal). Mucins, heme-oxygenase, and IgG chains were present in both glands. Proteome analysis by nano LC-MS/MS confirmed that several transcripts are expressed in the glands. The database presented herein is accessible online at http://exon.niaid.nih.gov/transcriptome/D_rotundus/Supplemental-web.xlsx. These results reveal that bat saliva emerges as a novel source of modulators of vascular biology. Biological significance: Vampire bat saliva emerges as a novel source of antihemostatics which modulate several aspects of vascular biology. © 2013.
Keywords: Bat ecology; Desmodus rotundus; Hematophagy; Illumina; Proteome; Vampire bat; ADAMTS1 protein; apyrase; cystatin; defensin; endonuclease; heme oxygenase; hypophysis adenylate cyclase activating polypeptide; immunoglobulin G; lactoferrin; lipocalin; lysozyme; messenger RNA; mucin; natriuretic peptide type C; phosphatase; plasminogen activator; prostaglandin; proteinase inhibitor; proteome; RNA; secretoglobin; sphingomyelin phosphodiesterase; tissue factor pathway inhibitor; transcriptome; amino acid sequence; animal experiment; bat; fibrinolysis; gene sequence; liquid chromatography; mass spectrometry; nonhuman; priority journal; protein analysis; protein binding; protein expression; rabies; submandibular gland